EFEITO DE CULTIVARES DE ALGODOEIRO (GOSSYPIUM HIRSUTUM L.) SOBRE ALGUNS ASPECTOS BIOLÓGICOS DAS FASES IMATURAS DE CHRYSOPERLA EXTERNA (HAGEN, 1861) (NEUROPTERA: CHRYSOPIDAE) - Pessoa, L.g.a. [UNESP] (2024)
The objective of this work was to evaluate the effect of the cotton cultivars Auburn SM 310, JPM 78188-3, Allen and IPEACO-SL 22-61131 on some biological aspects of the immature stages of Chrysoperla externa. The trials were conducted at 25 ± 2º C, 60 ± 10% RH and 12-hour photophase, in a completely randomized design. Newly hatched larvae were placed in Petri dishes containing leaf disks (5 cm in diameter) of those cultivars and fed on third and fourth instar nymphs of Aphis gossypii. In general, only the larval stage was affected by the cultivars. Auburn SM 310 cultivar caused an increase in the length of that stage and a reduction in the survival of the first instar. The trichomes on the leaves of the cotton cultivars did not affect the development time of the immature stages of C. externa. The negative effects on that stage caused by that cultivar maybe related to some resistance mechanism of a chemical nature.